A Novel Quantum Dot Fluorescence Immunosensor Based on Magnetic Beads and Portable Flow Cytometry for Detection of Okadaic Acid. (2017) - Pan, Yuxiang; Zhou, Jie; Su, Kaiqi; Hu, Ning; Wang, Ping
Abstract: Okadaic acid (OA) is a representative diarrhetic shellfish poisoning toxin which is highly toxic and carcinogenic to human, and rich in polluted shellfish. In this work, a novel and high sensitive fluorescence immunosensor based on magnetic beads (MBs) and quantum dots (QDs) had been developed for OA detection. Carboxylic acid modified MBs were used as supporter to immobilize the OA-BSA, competed with the OA in the sample solution to bind with the anti-OA monoclonal antibody (OA-MAb). The CdTe QDs (EX600 nm) labeled IgG was served as secondary antibody to perform fluorescence detection. A portable flow cytometry, Moxi Flow was applied for OA on-site quantification. The results showed that the OA concentration was inversely proportional to the QDs fluorescence intensity. The limit of detection (LOD) was 0.05 μg/L with a linear range of 0.2–20 μg/L for OA detection, which was far lower than traditional id-ELISA strategy. Moreover, OA detection for the real sample could be completed within 1 hour. The matrix effect and the recovery rate were also assessed during real sample measurement, showing a high recovery.